A High-accuracy Detection Method Research for Electric Power Harmonic - Jingfang Wang (Institute of Advanced Engineering and Science, 2014)
In this paper, a time-frequency filter is designed，which can detect the frequency, amplitude and phase of any order harmonics and interharmonics in signal by means of time domain convolution．The theory analysis are carried to this method and the calculate formula are concluded, the spectral leakage and the barrier domino offect are shun, the non-integer order wave are eluded, which are engendered in Fourier domain．Experiment simulation results show that time-frequency filtering convolution flunction can be designed and realized neatly and conveniently ; the influences of fundamental frequency fluctuation on harmonic analysis are restrained by using the approach presented in this paper；the relative errors of calculating fundamental frequencies with many order harmonics and interharmonics are no more than 0.00008%, the relative erors of calculating amplitudes are no more than 0.00013%，and those of calculating initial phases are no more than 0.078%． http://dx.doi.org/10.11591/telkomnika.v12i12.6474